Brazilian-Portuguese translation, cross-cultural adaptation and validation of the Myasthenia Gravis Composite scale. A multicentric study - Ezequiel Fernandes Oliveira; Valéria Cavalcante Lima; Eduardo Araujo Perez; Melissa Nunes Polaro; Berenice Cataldo Oliveira Valério; João R Pereiro; Sergio Roberto Nacif; Claudia Santos Oliveira; Acary Souza Bulle Oliveira; Luis Vicente Franco Oliveira (Arquivos de Neuro-Psiquiatria)
ABSTRACT Objective To perform the translation, cultural adaptation and validation of the Myasthenia Gravis Composite (MGC) scale in Brazil. Methods The study was conducted at three neuromuscular disease research centers in accordance with the international ethical standards, following a multi-modal approach and was conducted in three steps consisting of translation, cultural adaptation, and validation according to international guidelines. The final version of the MGC was applied in a sample of 27 MG patients and the total score was compared to a Portuguese version of the MG-QOL-15. Results The internal consistency verified by Cohen’s Kappa test was excellent (0.766). The correlation between the MGC and MG-QOL-15 was strong (R = 0.777; p = 0.000). No significant differences were found between the responses of patients in the first and second applications of the MGC. Conclusion The MGC scale, validated into Brazilian Portuguese, has proven to be a reliable instrument that is easy to use, and is highly reproducible.